An Xq22.1q22.2 nullisomy in a male patient with severe neurological impairment. Issue 4 (22nd March 2017) - Shirai, Kentaro; Higashi, Yuya; Shimojima, Keiko; Yamamoto, Toshiyuki
Abstract : The proteolipid protein 1 gene ( PLP1 ) is located on chromosome Xq22.2 and is related to X‐linked recessive leukoencephalopathy (Pelizaeus–Merzbacher disease: PMD). Compared to PLP1 duplications, which are a major contributor to PMD, chromosomal deletions in this region are rare and only a few PMD patients with small deletions have been reported, suggesting that large deletions of this region would cause embryonic lethality. Previously, we have reported female patients, with chromosomal deletions in this region, who showed severe developmental delays and behavioral abnormalities. In this study, we identified the first case of a male patient associated with an Xq22 nullisomy in a region proximal to PLP1 . The patient showed severe neurological impairment and was bedridden. Brain magnetic resonance imaging revealed a severely reduced cerebral volume. The chromosomal region proximal to PLP1 was considered to be significantly important for brain development.